Health outcomes and cost impact of the new WHO 2013 guidelines on prevention of mother-to-child transmission of HIV in Zambia. - Naoko Ishikawa (Public Library of Science (PLoS), 2014)
Background Countries are currently progressing towards the elimination of new paediatric HIV infections by 2015. WHO published new consolidated guidelines in June 2013, which now recommend either 'Antiretroviral drugs (ARVs) for women living with HIV during pregnancy and breastfeeding (Option B)' or 'Lifelong antiretroviral therapy (ART) for all pregnant and breastfeeding women living with HIV (Option B+)', while de facto phasing out Option A. This study examined health outcomes and cost impact of the shift to WHO 2013 recommendations in Zambia. Methods A decision analytic model was developed based on the national health system perspective. Estimated risk and number of cases of HIV transmission to infants and to serodiscordant partners, and proportions of HIV-infected pregnant women with CD4 count of ≤350 cells/mm3 to initiate ART were compared between 2010 Option A and the 2013 recommendations. Total costs of prevention of mother-to-child transmission of HIV (PMTCT) services per annual cohort of pregnant women, incremental cost-effectiveness ratio (ICER) per infection averted and quality-adjusted life-year (QALY) gained were examined. Results Our analysis suggested that the shift from 2010 Option A to the 2013 guidelines would result in a 33% reduction of the risk of HIV transmission among exposed infants. The risk of transmission to serodiscordant partners for a period of 24 months would be reduced by 72% with 'ARVs during pregnancy and breastfeeding' and further reduced by 15% with 'Lifelong ART'. The probability of HIV-infected pregnant women to initiate ART would increase by 80%. It was also suggested that while the shift would generate higher PMTCT costs, it would be cost-saving in the long term as it spares future treatment costs by preventing infections in infants and partners. Conclusion The shift to the WHO 2013 guidelines in Zambia would positively impact health of family and save future costs related to care and treatment.